Standardization and validation of real time PCR assays for the diagnosis of histoplasmosis using three molecular targets in an animal model (2017)
ABSTRACT: Histoplasmosis is considered one of the most important endemic and systemic mycoses worldwide. Until now few molecular techniques have been developed for its diagnosis. The aim of this study was to develop and evaluate three real time PCR (qPCR) protocols for different protein-coding genes (100-kDa, H and M antigens) using an animal model. Fresh and formalin-fixed and paraffin-embedded (FFPE) lung tissues from BALB/c mice inoculated i.n. with 2.5x106 Histoplasma capsulatum yeast or PBS were obtained at 1, 2, 3, 4, 8, 12 and 16 weeks post-infection. A collection of DNA from cultures representing different clades of H. capsulatum (30 strains) and other medically relevant pathogens (36 strains of related fungi and Mycobacterium tuberculosis) were used to analyze sensitivity and specificity. Analytical sensitivity and specificity were 100% when DNAs from the different strains were tested. The highest fungal burden occurred at first week post-infection and complete fungal clearance was observed after the third week; similar results were obtained when the presence of H. capsulatum yeast cells was demonstrated in histopathological analysis. In the first week post-infection, all fresh and FFPE lung tissues from H. capsulatum-infected animals were positive for the qPCR protocols tested except for the M antigen protocol, which gave variable results when fresh lung tissue samples were analyzed. In the second week, all qPCR protocols showed variable results for both fresh and FFPE tissues. Samples from the infected mice at the remaining times post-infection and uninfected mice (controls) were negative for all protocols. Good agreement was observed between CFUs, histopathological analysis and qPCR results for the 100-kDa and H antigen protocols. We successfully standardized and validated three qPCR assays for detecting H. capsulatum DNA in fresh and FFPE tissues, and conclude that the 100-kDa and H antigen molecular assays are promising tests for diagnosing this mycosis.